SAT0440 The IL-1RA Antagonist Kineret® (Anakinra) Stabilizes Hearing Loss in Patients with Severe Cryopyrin-Associated Periodic Syndromes (CAPS). (23rd January 2014) - Leinonen, M.; Söderberg, K.; Olivecrona, H.; Aldén Raboisson, M.; Sibley, C.; Brewer, C.; Plass, N.; King, K.; Zalewski, C.; Kim, J.; Stone, D.; Chapelle, D.; et al.
Abstract : Background: CAPS is a rare monogenic autoinflammatory syndrome consisting of a spectrum of three conditions: FCAS, Muckle-Wells syndrome (MWS), and the most severe form, NOMID/CINCA. Progressive hearing loss is a characteristic of severe CAPS 1 . Previous analyses showed that long-term Kineret treatment stabilized the progression of hearing loss 2 . Objectives: To evaluate whether long-term Kineret treatment stabilizes hearing loss among pediatric patients, with focus on the subset of infants/toddlers. Methods: A prospective open-label study with long-term extension including 43 patients was conducted at the National Institutes of Health (NIH study 03-AR-0298) 1, 2 . The patients were classified as children (age < 12 years) or adolescents/adults (age ≥ 12 years) based on age at Kineret treatment start. Focus was put on the subgroup of infants/toddlers (age<2 years at treatment start). Hearing was monitored with audiogram and by presence of lesions in the cochlea for up to 5 years. The audiogram was evaluated with four frequency (0.5/1/2/4 kHz) pure tone average (4F-PTA), based on both air and bone conduction in the ear with best and worst hearing. The longitudinal changes in 4F-PTA were estimated with a mixed model for repeated measures (MMRM). Results: The baseline 4F-PTA correlated with age at treatment start so that older patients presented with more hearing loss. The MMRM analysis of 4F-PTA included 12 children (median follow-up (FU) 60 months) and 9 adolescents/adults (median FU 54 months). The mean (SD) baseline 4F-PTA in the best ear based on air conduction was 27.6 (19.6) dB HL in children and 53.5 (32.2) dB HL in adolescents/adults. No significant changes were seen in mean 4F-PTA at any time point up to 5 years in either children or adolescents/adults; thus, hearing remained stable. The estimated change from baseline to 5 years was -1.0 dB HL (95% CI -8.6 to 6.6) in children and 2.7 dB HL (95% CI -2.1 to 7.5) in adolescents/adults. Comparable findings were seen in the worst ear and for both ears based on bone conduction assessments. In the subset of 5 infants/toddlers (median FU 48 months), the audiogram monitoring was started after 1-3 years of treatment. The hearing in the best ear remained normal (4F-PTA ≤20 dB HL) in all infants/toddlers at all visits except one transient elevation to 21 dB HL. One of the 5 infants/toddlers presented with a moderate conductive hearing loss (4F-PTA 65 dB HL) in the worst ear associated with middle ear effusion. The audiogram results were supported by non-increased proportion of cochlear enhancement. Conclusions: Correlation between the audiogram and age at treatment start is consistent with progressive hearing loss observed in untreated NOMID patients. Kineret treatment for up to 5 years stabilized the progression of hearing loss in both pediatric and adolescent/adult patients as well as in infants/toddlers. Efforts should be made for early diagnosis of the disease and early treatment initiation. References: Goldbach-Mansky et al. N Engl J Med 2006;355:581–92. Sibley et al. Arthritis Rheum 2012;2375–86 Disclosure of Interest: M. Leinonen Consultant for: Swedish Orphan Biovitrum AB, K. Söderberg Employee of: Swedish Orphan Biovitrum AB, H. Olivecrona Employee of: Swedish Orphan Biovitrum AB, M. Aldén Raboisson Employee of: Swedish Orphan Biovitrum AB, C. Sibley: None Declared, C. Brewer: None Declared, N. Plass: None Declared, K. King: None Declared, C. Zalewski: None Declared, J. Kim: None Declared, D. Stone: None Declared, D. Chapelle: None Declared, R. Goldbach-Mansky Grant/research support from: Swedish Orphan Biovitrum AB, Regeneron, and Novartis